2010
DOI: 10.1016/j.mce.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Two insulin-like peptide family members from the mosquito Aedes aegypti exhibit differential biological and receptor binding activities

Abstract: Insects encode multiple ILPs but only one homolog of the vertebrate IR that activates the insulin signaling pathway. However, it remains unclear whether all insect ILPs are high affinity ligands for the IR or have similar biological functions. The yellow fever mosquito, Aedes aegypti, encodes eight ILPs with prior studies strongly implicating ILPs from the brain in regulating metabolism and the maturation of eggs following blood feeding. Here we addressed whether two ILP family members expressed in the brain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 51 publications
(102 reference statements)
4
98
0
Order By: Relevance
“…This type of signaling regulation may also occur in insects. Wen et al (Wen et al, 2010) showed that A. aegypti ILP3 bound to MIR in isolated ovary membranes with much higher affinity than did ILP4 or bovine insulin, indicating that the MIR varies in its affinity for endogenous ILPs as well as for mammalian insulin. Similarly, the Drosophila melanogaster insulin receptor can respond to different ILP ligands, as shown by the ability of DILP5 isoforms and IGFs to competitively displace human insulin from the fruit fly insulin receptor (Sajid et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This type of signaling regulation may also occur in insects. Wen et al (Wen et al, 2010) showed that A. aegypti ILP3 bound to MIR in isolated ovary membranes with much higher affinity than did ILP4 or bovine insulin, indicating that the MIR varies in its affinity for endogenous ILPs as well as for mammalian insulin. Similarly, the Drosophila melanogaster insulin receptor can respond to different ILP ligands, as shown by the ability of DILP5 isoforms and IGFs to competitively displace human insulin from the fruit fly insulin receptor (Sajid et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Aedes aegypti ILP3 (AaILP3) and ILP4 (AaILP4) were synthesized as previously described (Brown et al, 2008;Wen et al, 2010). 20E (Sigma) was solubilized in absolute ethanol.…”
Section: Reagentsmentioning
confidence: 99%
“…10902, Gibco, Gaithersburg, MD, USA) alone or with other reagents. ECD content in each sample of medium (50l) was determined by radioimmunoassay (RIA) (Wen et al, 2010). Total protein was determined for abdomen walls (i.e.…”
Section: First Clutch In Vivo Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in A. aegypti also establish that ILP3 activity depends upon binding to the insulin receptor (IR), a receptor tyrosine kinase (RTK), which triggers phosphorylation of downstream components in the insulin signaling pathway including Akt (4,9,14). OEH in contrast belongs to a poorly characterized family of neuropeptides known only from arthropods called neuroparsins (13,15,16).…”
mentioning
confidence: 99%